Історія слів діловодство / справочинство в лексикографічній практиці ХХ – початку ХХІ століть - Боярчук, О. (Лексикографічний бюлетень, 2012)
The article is dedicated to the issue of functioning of two Ukrainian synonymic official-business language terms діловодство and справочинство that are counterparts of the Russian term «делопроизводство» («деловодство»). The history of translation of this Russian term and its derivatives into Ukrainian language was analyzed. As a material 32 dictionaries (mostly Russian-English official-business language dictionaries) of the 20th – the beginning of the 21st centuries were chosen.